Berberine radiosensitizes human nasopharyngeal carcinoma by suppressing hypoxia-inducible factor-1α expression. (February 2014) - Zhang, Chi; Yang, Xi; Zhang, Qu; Yang, Baixia; Xu, Liping; Qin, Qin; Zhu, Hongcheng; Liu, Jia; Cai, Jing; Tao, Guangzhou; Ma, Jianxin; Ge, Xiaolin; et al.
Abstract Conclusion: Berberine confers radiosensitivity on nasopharyngeal carcinoma (NPC) and this is associated with the down-regulation of hypoxia-inducible factor-1α (HIF-1α) and vascular endothelial growth factor (VEGF) expression. Berberine could be a promising radiosensitizer for NPC radiotherapy. Objectives: NPC has a poor prognosis. Radiotherapy as first-line therapy significantly increases patient survival but radioresistance is a problem. This study aimed to investigate the radiosensitizing effects of berberine on NPC and explore the underlying mechanisms. Methods: CNE-1 and CNE-2 cells were exposed to hypoxia and treated with berberine at different concentrations. The MTT assay, clonogenic assay, and flow cytometry were performed to analyze cell proliferation, colony formation, and apoptosis. The expression of HIF-1α and VEGF was assessed by Western blot and immunofluorescence analysis. Male nude mice inoculated subcutaneously with CNE-2 cells were used to examine the sensitizing effects of berberine in vivo.Results: Berberine efficiently radiosensitized NPC cells and xenografts in mice, and inhibited hypoxia/radiation-induced up-regulation of HIF-1α and VEGF expression.